Optimization of Selected Agricultural Export Commodities to Improve Indonesia’s Weaponry Countertrade - Arifin, Zainal; Suman, Agus; Khusaini, Moh. (International Journal of Criminology and Sociology, 2021)
In an increasingly open global economy, international trade, including exports, is an inseparable part of economic activity between countries. This paper aims to analyze the choice of commodities that have the potential to encourage the implementation of defense equipment trade-in Indonesia along with some optimization efforts. Using the literature review and library research by exploring data of national agricultural export and arms trade, this article identifies selected commodities that have the potential to be exchanged with defense equipment in trade returns, and also attempts to optimize exports to encourage the implementation of trade returns themselves. The results showed that trade return is one of the schemes in international trade in the form of two-way sales. The weaponry system is a strategic product that is still imported by Indonesia from abroad so that it has the potential to be implemented in a trade return scheme. On the other hand, Indonesia is known to excel in agricultural products, especially the plantation subsector, and has succeeded in becoming the top exporters for many agricultural commodities in the global market.